Characterization of the lightning activity of “Relámpago del Catatumbo” - Burgesser, Rodrigo Exequiel (2012)
The “Relámpago del Catatumbo” (Catatumbo Lightning) is a phenomenon known for more than 500 years that occurs in Venezuela. This phenomenon occurs almost all along the year in a very small region of the southwest region of Maracaibo Lake and, according to the Lightning Imaging Sensor (LIS) data, this region presents the highest lightning activity of the world. The region presents a complex topography with particular climatic conditions. The lightning activity of the region was examined using the World Wide Lightning Location Network (WWLLN) data. The results show two very localized high-lightning activity centers: one of them is confined around [9.5°N; 71.5°W] over the southwest region of the Maracaibo Lake, and the other is around [9°N; 73°W] near the Colombia–Venezuela border. The lightning activity has a semiannual behavior with two maxima, one around May and another one around October. The diurnal cycle shows substantial lightning activity during local nights.